Welfare Analysis Through Human Development Index with Maqasid Sharia Approach - Prima Dwi Priyatno; Fitri Yetty; Lili Puspita Sari; Ahmad Zahran Rizqulloh (Journal of Islamic Economics and Finance Studies, 2023)
The existing Human Development Index (HDI), published by UNDP may be the most comprehensive indicator. Even though, it is not fully compatible and sufficient to measure human development from an Islamic perspective. The purpose of this study is to analyze the Human Development Index in Indonesia with the maqasid sharia approach using several indicators that include crime, life expectancy, long school expectancy, average length of schooling, births, infant mortality, and per capita expenditure. The measurement results show variations in I-HDI from year to year, with the highest value in 2022 and the lowest in 2021. The I-HDI categorization classifies 2017, 2018, 2019, and 2022 as very high categories, while 2020 and 2021 are in the high category. The factors that make up I-HDI are divided between the Material Welfare Index (MWI) and the Non-Material Welfare Index (NWI). Although MWI showed low numbers, NWI made a significant positive contribution. NWI has a dominant role, with the highest score in 2017 and an average of 83.58 percent. This finding implies that Non-Material Welfare is a key factor in shaping I-HDI in Indonesia. These conclusions can be used as a basis for formulating more effective development policies, reinforcing aspects that are considered lacking, and providing guidance for future policy considerations.   Indeks Pembangunan Manusia (IPM) yang diterbitkan oleh UNDP dapat menjadi indikator yang paling komprehensif. Namun, alat ukur tersebut tidak sepenuhnya kompatibel dan memadai untuk mengukur pembangunan manusia jika ditinjau dalam perspektif Islam. Tujuan penelitian ini adalah menganalisis Indeks Pembangunan Manusia di Indonesia dengan pendekatan maqashid syariah yang meliputi beberapa indikator seperti kriminalitas, angka harapan hidup, lama sekolah, rata-rata lama sekolah, kelahiran, kematian bayi, dan pengeluaran per kapita. Hasil pengukuran menunjukkan adanya variasi I-HDI dari tahun ke tahun, dengan nilai tertinggi pada tahun 2022 dan terendah pada tahun 2021. Kategorisasi I-HDI mengklasifikasikan tahun 2017, 2018, 2019, dan 2022 dalam kategori sangat tinggi, sedangkan tahun 2020 dan 2021 termasuk dalam kategori tinggi. Faktor-faktor pembentuk I-HDI terbagi menjadi Indeks Kesejahteraan Material (MWI) dan Indeks Kesejahteraan Non-Material (NWI). Meski MWI menunjukkan angka yang rendah, namun NWI memberikan kontribusi positif yang signifikan. NWI mempunyai peran dominan dengan skor tertinggi pada tahun 2017 dan rata-rata mencapai 83,58 persen. Implikasi dari temuan ini menunjukkan bahwa kesejahteraan non-material menjadi faktor kunci dalam pembentukan I-HDI di Indonesia. Kesimpulan tersebut dapat dijadikan landasan untuk merumuskan kebijakan pembangunan yang lebih efektif untuk memperkuat aspek-aspek yang dianggap kurang optimal, dan memberikan pedoman pertimbangan kebijakan di masa depan.